= 2x – 1 = -3
2x = -3 + 1 = -2
= x = -1
Rate this question :
How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
view all courses
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
RELATED QUESTIONS :
Find the value ofNCERT - Mathematics Exemplar
State whether theNCERT - Mathematics Exemplar